Communication skills training for improving the communicative abilities of student social workers: A systematic review - Emma Reith‐Hall; Paul Montgomery (Campbell Systematic Reviews, 2023)
Abstract Background Good communication is central to effective social work practice, helping to develop constructive working relationships and improve the outcomes of people in receipt of social work services. There is strong consensus that the teaching and learning of communication skills for social work students is an essential component of social work qualifying courses. However, the variation in communication skills training and its components is significant. There is a sizeable body of evidence relating to communication skills training therefore a review of the findings helps to clarify what we know about this important topic in social work education. We conducted this systematic review to determine whether communication skills training for social work students works and which types of communication skills training, if any, were more effective and lead to the most positive outcomes. Objectives This systematic review aimed to critically evaluate all studies which have investigated the effectiveness of communication skills training programmes for social work students. The research question which the review posed is: ‘What is the effectiveness of communication skills training for improving the communicative abilities of social work students?’ It was intended that the review would provide a robust evaluation of communication skills training for social work students and help explain variations in practice to support educators and policy‐makers to make evidence‐based decisions in social work education, practice and policy. Search Methods We conducted a search for published and unpublished studies using a comprehensive search strategy that included multiple electronic databases, research registers, grey literature sources, and reference lists of prior reviews and relevant studies. Selection Criteria Study selection was based on the following characteristics: Participants were social work students on generic (as opposed to client specific) qualifying courses; Interventions included any form of communication skills training; eligible studies were required to have an appropriate comparator such as no intervention or an alternative intervention; and outcomes included changes in knowledge, attitudes, skills and behaviours. Study selection was not restricted by geography, language, publication date or publication type. Data Collection and Analysis The search strategy was developed using the terms featuring in existing knowledge and practice reviews and in consultation with social work researchers, academics and the review advisory panel, to ensure that a broad range of terminology was included. One reviewer conducted the database searches, removing duplicates and irrelevant records, after which each record was screened by title and abstract by both reviewers to ensure robustness. Any studies deemed to be potentially eligible were retrieved in full text and screened by both reviewers. Main Results Fifteen studies met the inclusion criteria. Overall, findings indicate that communication skills training including empathy can be learnt, and that the systematic training of social work students results in some identifiable improvements in their communication skills. However, the evidence is dated, methodological rigour is weak, risk of bias is moderate to high/serious or incomplete, and extreme heterogeneity exists between the primary studies and the interventions they evaluated. As a result, data from the included studies were incomplete, inconsistent, and lacked validity, limiting the findings of this review, whilst identifying that further research is required. Authors’ Conclusions This review aimed to examine effects of communication skills training on a range of outcomes in social work education. With the exception of skill acquisition, there was insufficient evidence available to offer firm conclusions on other outcomes. For social work educators, our understanding of how communication skills and empathy are taught and learnt remain limited, due to a lack of empirical research and comprehensive discussion. Despite the limitations and variations in educational culture, the findings are still useful, and suggest that communication skills training is likely to be beneficial. One important implication for practice appears to be that the teaching and learning of communication skills in social work education should provide opportunities for students to practice skills in a simulated (or real) environment. For researchers, it is clear that further rigorous research is required. This should include using validated research measures, using research designs which include appropriate counterfactuals, alongside more careful and consistent reporting. The development of the theoretical underpinnings of the interventions used for the teaching and learning of communication skills in social work education is another area that researchers should address.